Super nets for supercomputers. - Cass, S.
Supercomputers to date have been accessible to only a few fortunate specialists. But a new era will use high-speed data networks to link the huge beasts to more and more researchers' desktops, and just as important, to link individual supercomputers together. These new networks, or grids, are needed to grapple with incredible volumes of data and in turn promise better and cheaper science. With grids, massive amounts of communal data can be stored and processed independently of individual research groups and on the most appropriate resources. Grids also encourage better analyses
Keywords: Communal data processing; Communal data storage; High-speed data networks; Networked supercomputers; Supercomputers network